Pelaksanaan Perlindungan Hukum Bagi Wajib Pajak Kendaraan Bermotor di Kabupaten Tabanan pada Masa Pandemi Covid 19 - A A Gd Jelantik Wisnu Putra; Ida Ayu Putu Widiati; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2022)
The impact given by the COVID-19 pandemic is felt so widely in various sectors including in terms of regional income, especially on vehicle taxes, the motorcycle tax itself is a regional tax. Therefore, this research aims to find out the procedures for implementing motor vehicle tax collection during the covid 19 pandemic and to find out legal protection for motor vehicle taxpayers in Tabanan district. In conducting research, empirical research is used which is obtained from the results of observing real events in the field. The results of this research in the implementation of motor vehicle tax collection in Tabanan district based on the regional regulation of the province of Bali Number 1 of 2011, during the covid 19 pandemic it did not run effectively due to a decrease in motor vehicle tax payment income which mostly had an impact on the economic sector, obstacles in paying taxes on During the pandemic, taxpayers who paid taxes decreased which resulted in decreased local revenue. Legal protection for taxpayers in the event of a tax dispute, the taxpayer can file an objection or appeal, preventive and repressive measures are efforts to resolve tax disputes.